Sosialisasi dan Pelatihan Penerapan Teknologi yang Tepat untuk Pengelolaan Limbah Rumah Tangga di Kampung Arar Kabupaten Sorong - Rahmatullah, Azwar; Ibal, La; Maysyurah, Alfina; Murni; Nurbia; Yasin, Azalia Fajri; Marasabessy, Umar R.; Madaul, Rahful A.; Abubakar, Endang (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
Household waste management in Sorong Regency, especially in Arar Village, faces major challenges in reducing negative impacts on the environment. One effective solution is processing organic waste into liquid organic fertilizer (POC). This fertilizer not only reduces the amount of waste but can also increase soil fertility and support more sustainable agriculture. The Community Service Program (PKM) implemented in Arar Village aims to provide training to the community, farmer groups, and PKK mothers on how to make POC from household waste. The methods used in this program include socialization, training, and direct practice of making liquid organic fertilizer using natural ingredients and bioactivators such as EM4. After the training, 80 percent of participants successfully applied the knowledge gained to produce liquid organic fertilizer, which has been proven to increase agricultural yields and support environmental sustainability. The evaluation results show that this program provides significant benefits in reducing dependence on chemical fertilizers and increasing public awareness of the importance of environmentally friendly waste management.